Essentials of microeconomics - Nguyen, Bonnie; Wait, Andrew (Routledge, Taylor & Francis Group, 2024)
"Essentials of Microeconomics is an excellent introduction to microeconomics. It presents the basic tools of microeconomics clearly and concisely. It presents a vigorous treatment of all relevant introductory microeconomic concepts, and emphasizes on modern economics - game theory and imperfect markets. Each chapter is self-contained and includes the required key mathematical skills at the start. Now in its second edition, this updated textbook includes: Expanded lecturer resources, including detailed lecture slides, sample exam questions and updated test bank MCQs An additional section on Economics in Practice, focused on policy, econometrics, and behavioural economics This book is ideal not only for introductory microeconomics course, but its level of analysis also makes the book appropriate for introductory level economics taught at postgraduate level. With the emphasis on strategy, this text is also well suited for use in business economics courses"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Microeconomics; Microéconomie